Development of Mother’s Behavior Model in Severe Malnutrition Prevention for Under Five Children - Ika Nur Fauziah; Lilik Djuari; Yuni Sufyanti Arief (Jurnal Ners, 2015)
Introduction: Child malnutrition still a major health problem in the world, including in Indonesia. According to World Health Organization (WHO) African Region and South-East Asia Region data, malnutrition affects nearly 20 million under five children and the main factors that affects about a third of child mortality worldwide. The aims of this study was to analyze and develop mother’s behavior model in severe malnutrition prevention for under five children based on Integration Health Belief Model and Health Promotion Model.Method: Type of this research was an explanatory observational with cross sectional design. Affordable population namely children under five’s years and cadres who visited Posyandu in April 2015 as many as 136 and 20 peoples. This study used proportional random sampling, with sample size 65 mothers; 10 children under five’s mothers and 10 Posyandu Balita’s cadres for FGD. Variables were personal factors, behavioral specific cognitions and affect, individual perceptions, commitment, cues to action and mother's behavior in severe malnutrition prevention. Data were collected by using questionnaires and food recall 24 hours, analyzed by Smart PLS.Result: Mother’s behavior model in severe malnutrition prevention for under five children can be formed by mother's commitment, behavioral specific cognition and affect and personal factors (income and motivation).Discussion: Nurse as a community health care providers have a role in improving community health status through health promotion. High commitment to behave in certain ways according to plan, improving the ability of individuals to maintain health promotion behavior all the time.